2014
DOI: 10.1016/j.jim.2014.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Toward development of a comprehensive external quality assurance program for polyfunctional intracellular cytokine staining assays

Abstract: The External Quality Assurance Program Oversight Laboratory (EQAPOL) Flow Cytometry Program assesses the proficiency of NIH/NIAID/DAIDS-supported and potentially other interested research laboratories in performing Intracellular Cytokine Staining (ICS) assays. The goal of the EQAPOL Flow Cytometry External Quality Assurance Program (EQAP) is to provide proficiency testing and remediation for participating sites. The program is not punitive; rather, EQAPOL aims to help sites identify areas for improvement. EQAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The EQAPOL program currently administers three EQA programs: the interferon-γ T cell ELISpot assay (see (Sanchez et al, 2014b)), the Luminex based cytokine bead-based array assays (see (Lynch et al, 2014)), and the polychromatic flow cytometry-based intracellular cytokine staining (ICS) assays (Staats et al, 2014). Sanchez et al provides a detailed description of the development of an external proficiency testing program designed to assess individual sites’ performance of the interferon-γ T cell ELISpot assay.…”
Section: Eqa Programsmentioning
confidence: 99%
“…The EQAPOL program currently administers three EQA programs: the interferon-γ T cell ELISpot assay (see (Sanchez et al, 2014b)), the Luminex based cytokine bead-based array assays (see (Lynch et al, 2014)), and the polychromatic flow cytometry-based intracellular cytokine staining (ICS) assays (Staats et al, 2014). Sanchez et al provides a detailed description of the development of an external proficiency testing program designed to assess individual sites’ performance of the interferon-γ T cell ELISpot assay.…”
Section: Eqa Programsmentioning
confidence: 99%
“…The Duke University Human Vaccine Institute (DHVI) has been the central laboratory of the National Institute of Health/National Institute of Allergy and Infectious Diseases (NIH/NIAID) External Quality Assurance Program Oversight Laboratory (EQAPOL) through a Department of Health and Human Services contract since September 2010. As part of this program, EQAPOL has developed and run PT programs for Interferon-gamma (IFN- γ ) Enzyme-linked immunosorbent spot (ELISpot), multiparameter Intracellular Cytokine Staining (ICS) Flow Cytometry and Luminex bead-based multiplex cytokine assays (Lynch et al, 2014; Rountree et al, 2014; Sanchez et al, 2014; Staats et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Both IFN- γ ELISpot and ICS assays, performed to evaluate antigen-specific immune responses, have been subjected to validation procedures (Russell et al, 2003; Horton et al, 2007) according to Good Clinical Laboratory Practice (GCLP) guidelines, and the assays have been performed by EQAPOL laboratories accordingly (Sanchez et al, 2014; Staats et al, 2014). In the germinal paper that compared the performance of the ELISpot assay conducted by several different laboratory sites (Cox et al, 2006; Sanchez et al, 2014), several reagents were found to be key in the overall performance of the assay across laboratories with fetal bovine serum (FBS) being one of them (Cox et al, 2006; Janetzki et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Lyophilization is one method to stabilize antibody‐conjugate reagents via sublimation of the majority of aqueous and adsorbed water, in order to greatly decrease the potential for hydrolytic degradation of protein or fluorophore. We have developed improved techniques to lyophilize multicolor antibody cocktails in both 12 × 75 mm tube (Lyotube) and 96‐well plate (BD Lyoplate ™) formats . Multiple researchers have since used these lyophilized products and published their results in peer‐reviewed journals .…”
mentioning
confidence: 99%
“…We have developed improved techniques to lyophilize multicolor antibody cocktails in both 12 × 75 mm tube (Lyotube) and 96‐well plate (BD Lyoplate ™) formats . Multiple researchers have since used these lyophilized products and published their results in peer‐reviewed journals . In order to be of value to the utmost potential, multicolor reagent stabilizing technologies must yield the expected quality and functional performance characteristics as well as be robust and able to serve the various applications in the field of flow cytometry.…”
mentioning
confidence: 99%